Effects of Berberine and Its Derivatives on Cancer: A Systems Pharmacology Review - Zhang, Chaohe; Sheng, Jiyao; Li, Guangquan; Zhao, Lihong; Wang, Yicun; Yang, Wei; Yao, Xiaoxiao; Sun, Lihuan; Zhang, Zhuo; Cui, Ranji (Frontiers in Pharmacology, 2020)
Numerous studies have shown that berberine and its derivatives demonstrate important anti-tumor effects. However, the specific underlying mechanism remains unclear. Therefore, based on systems pharmacology, this review summarizes the information available on the anti-tumor effects and mechanism of berberine and its derivatives. This systems pharmacology review systematically examines the action and potential mechanism of action of berberine and its derivatives, used in the treatment of complex cancers, at the molecular, cellular, and organismic levels. Moreover, with further in-depth investigations on the toxicity and efficacy, berberine and its derivatives could be potential drugs in cancer therapy, with improved clinical efficacy and safety.